1981
DOI: 10.1021/jm00135a013
|View full text |Cite
|
Sign up to set email alerts
|

Puromycin analogs. Effect of aryl-substituted puromycin analogs on the ribosomal peptidyltransferase reaction

Abstract: A series of ortho- and para-substituted L-phenylalanylpuromycin analogues were synthesized and evaluated as substrates for the peptidyltransferase reaction of Escherichia coli ribosomes. Kinetic results reveal that substitution of the p-methoxy group of the puromycin molecule alters the peptidyltransferase activity of the molecule with the following decreasing order of substrate efficiencies: p-NH2 greater than p-NHCOCH3 greater than p-NO2 = p-NHCO(CH2)2CH3 greater than p-NHCOCH2Br. However, the inability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…fluorescence microscopy and for isolation by affinity chromatography. Structure-activity studies of puro (20)(21)(22)(23)(24) indicated that the molecule tolerates modifications of the O-Me phenyl ring, without significant loss of activity. We synthesized O-propargylpuromycin (OP-puro, Fig.…”
mentioning
confidence: 99%
“…fluorescence microscopy and for isolation by affinity chromatography. Structure-activity studies of puro (20)(21)(22)(23)(24) indicated that the molecule tolerates modifications of the O-Me phenyl ring, without significant loss of activity. We synthesized O-propargylpuromycin (OP-puro, Fig.…”
mentioning
confidence: 99%
“…[9] We also hoped to develop new PO-based pairs that could be used in multiplexed experiments similar to the AHA/HPG pair. [10] PO is known to be reasonably amenable to structural modifications, [11] and several PO-modified probes were already used in cell-free protein synthesis systems (Supporting Information, Figure S1B); [12] in some cases,s ignificant changes at the 5'-OH site of the aminonucleoside structure were tolerated. Herein, we report the development of six new PO analogues (AZ/BY/5N/5T/5Y/5Z in Figure 1A), all of which were capable of puromycylation in live mammalian cells,a lbeit with different incorporation efficiencies,a nd could be used for subsequent imaging and profiling of newly synthesized proteins.Bytaking advantage of the mutual orthogonality in some probes (5Y/5T and 5Z/5T), we showed they could be used in multiplexed experiments for labeling and simultaneous imaging of different protein populations,u nder both fixed and live-cell conditions.P rotein enrichment and identification were confirmed with select probes by large-scale pull-down (PD)/LC-MS/MS experiments.F inally,q uantita- tive measurement of protein dynamics was performed with labeled live mammalian cells and neurons by fluorescence correlation spectroscopy (FCS).…”
mentioning
confidence: 99%
“…We also hoped to develop new PO ‐based pairs that could be used in multiplexed experiments similar to the AHA/HPG pair . PO is known to be reasonably amenable to structural modifications, and several PO ‐modified probes were already used in cell‐free protein synthesis systems (Supporting Information, Figure S1B); in some cases, significant changes at the 5′‐OH site of the aminonucleoside structure were tolerated. Herein, we report the development of six new PO analogues ( AZ / BY / 5N / 5T / 5Y / 5Z in Figure A), all of which were capable of puromycylation in live mammalian cells, albeit with different incorporation efficiencies, and could be used for subsequent imaging and profiling of newly synthesized proteins.…”
Section: Figurementioning
confidence: 99%